49. Disrupted autonomic control in spinal cord injury. Issue 4 (April 2016) - Bongiovanni, L.G.; Barbieri, F.; Rossini, F.; Brigo, F.; Paluani, F.; Fondrieschi, L.; Marchi, S. De; Monaco, S.
Abstract : To investigate residual cholinergic and adrenergic responses to orthostatic stimulus in spinal cord injury, we evaluated 10 subjects with different outcome of traumatic (5) and inflammatory (5) spinal cord lesions between C6 and T10. The power spectra analysis of blood pressure and heart rate variability was performed during resting condition and head up tilt test. The difference between these two conditions was tested by using Wilcoxon signed rank test and the results were compared with control subjects. The typical decrease of HF power of R-R interval during posture changing was obtained only in the control subjects and in patients with paraplegia and incomplete lesions. In such conditions the SSR was always present at the plantar side. In complete lesions, the reduced decrease of HF is probably due to the down – regulation of vagal activity. In the same patients the absence of both heart rate and blood pressure LF peak are associated with the presence of some LF power of SBP. This seems to indicate the possibility of a LF generation either at a spinal level, without supraspinal control, or by other mechanisms, like the myogenic vasoconstrictor reflexes.